PARADOXES IN UNDERSTANDING PROFESSIONAL DEFORMATIONS OF AN INDIVIDUAL - N. S. Pryazhnikov; M. V. Polevaya; E. V. Kamneva (Финансы: теория и практика, 2017)
Today, there is no unambiguous definition of the phenomenon of professional deformation of an individual, which makes it impossible to separate the professional deformation from common errors in work, inadequate education of managers, normal fatigue, workaholism and professional “burnout”. An important feature of professional deformations is their gradual development in the process of activity and unawareness thereof by the employee. The lack of clear qualification requirements in the case when negative qualities are compensated with positive qualities often allowing the employee to perform his duties effectively lead to the fact that the professional deformation is not taken into account by the management. One of the problems of the professional deformation phenomenon is that the professional and personal deformations may not match and even contradict each other. The professional deformation is also developed if there is a mismatch between the education and the requirements of a particular job. The experience in different occupations, in addition to the development of positive qualities of a professional, often contributes to the development of negative qualities, i.e., professional deformations produced by various activities. The paper demonstrates the ambiguous relationship between professional deformations and professional incompetence, inadequate professional and life experience, common errors in professional activities. For every of such “paradoxes” general preventive measures are proposed not to allow these phenomena to escalate into a real professional deformation.